An unconstrained monitoring system for home rehabilitation. - Masuda, Y.
This study described a niche telemedicine framework for home healthcare. The framework aims to transmit small but sufficient amounts of data for daily monitoring of residential subjects' basic health status. As a proof of concept, an unconstrained monitoring system of heart/respiration rates using wireless telecommunication as an application for home-visit rehabilitation therapists was developed. The system allows a nomadic home-visit therapist to acquire the health information of a patient remotely - from anywhere at any time. It consists of a sensory system for the patient and a viewer system for the therapist. A TCP/IP network connects the subsystems using a physical communication infrastructure. The proposed system showed its usefulness for both the therapist and the patient in planning and evaluating daily rehabilitation training.
Keywords: TCP/IP network; Heart rate; Home healthcare; Home rehabilitation; Home-visit rehabilitation therapists; Respiration rate; Sensory system; Telemedicine; Unconstrained monitoring system; Wireless telecommunication